Charge Transport: Precise Control of Interfacial Charge Transport for Building Functional Optoelectronic Devices (Adv. Mater. Technol. 5/2019). Issue 5 (10th May 2019) - Zhang, Weining; Chen, Hongliang; Guo, Xuefeng
Abstract : In article number1800358, Weining Zhang, Hongliang Chen, and Xuefeng Guo developed an interface engineering methodology to functionalize the semiconductor/dielectric interface in an organic field‐effect transistor, thus leading to a photoactive nonvolatile memory device. This device has been arrayed into a photosensor matrix on flexible plastic substrates to detect the spatial distribution of confined light with high precision.